2017
DOI: 10.1101/225441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Gene Regulatory Landscape in 1,188 Human Tumors

Abstract: Cancer is characterised by somatic genetic variation, but the effect of the majority of non-coding somatic variants and the interface with the germline genome are still unknown. We analysed the whole genome and RNA-Seq data from 1,188 human cancer patients as provided by the Pan-cancer Analysis of Whole Genomes (PCAWG) project to map cis expression quantitative trait loci of somatic and germline variation and to uncover the causes of allele-specific expression patterns in human cancers. The availability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…We lastly sought to evaluate the source of the significant eQTLs we detect in CBCS. Similar to previous pan-cancer germline eQTL analyses [25], we cross-referenced eGenes found in CBCS with eGenes detected in relevant healthy tissues from Genotype-Tissue Expression (GTEx) Project. We attributed all but 7 of the cis-eGenes from CBCS across both AA and WW women found in GTEx to one of these three tissue types (Figure 1B), with the effect sizes of the top eQTLs for these eGenes correlating very well between CBCS and GTEx (see Supplemental Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…We lastly sought to evaluate the source of the significant eQTLs we detect in CBCS. Similar to previous pan-cancer germline eQTL analyses [25], we cross-referenced eGenes found in CBCS with eGenes detected in relevant healthy tissues from Genotype-Tissue Expression (GTEx) Project. We attributed all but 7 of the cis-eGenes from CBCS across both AA and WW women found in GTEx to one of these three tissue types (Figure 1B), with the effect sizes of the top eQTLs for these eGenes correlating very well between CBCS and GTEx (see Supplemental Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…We re-ran stratAS on each H3K27ac sample independently, restricted to peaks with high power to detect imbalance (having a total >50 reads across all heterozygous sites in the peak). We then built a logistic regression across all individual-peak pairs, with the presence/absence of a significant T-/d-asQTL as the outcome and various local features as predictors (mirroring similar analyses of allele-specific expression in previous work 22 ). We found that the presence of an SCNA loss was the feature most predictive of a T-asQTL (OR of 3.5, explaining 9.6% of variance) followed by the presence of an N-asQTL in the matched normal (OR of 5.24, but explaining 2.9% of variance) ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The traditional approach of inferring hidden confounders using principal component or factor analysis 19 typically separates all tumor/normal samples and would thus result in an undefined or unstable interaction test. The allelic imbalance model has been applied extensively in studies of normal expression, but no formal interaction test has been proposed, and the previous applications to cancer have not modelled tumor-specific structural variation that can introduce biases 2022 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, EA tumor-specific eGenes showed enrichments for cell death and proliferation ontologies, and immune-specific eGenes showed cytokine and lymph vessel-associated processes. We then cross-referenced bulk and tumor-specific cis -eGenes found in the CBCS EA sample with cis -eGenes detected in healthy tissues from GTEx: mammary tissue, fibroblasts, lymphocytes, and adipose (see Materials and Methods), similar to previous pan-cancer germline eQTL analyses ( 10 , 110 ). We attributed several of the bulk cis -eGenes to healthy GTEx tissue (all but 2), but tumor-specific cis -eGenes were less enriched in healthy tissues ( Supplemental Figure S21 ).…”
Section: Resultsmentioning
confidence: 99%